Quality of Life Among Diabetic Patients Using Transtibial Prostheses: A Descriptive Study - Setyawan, Dwi; Fatati, Muhibbah (P3M Universitas 'Aisyiyah Surakarta, 2025)
Background Diabetes mellitus (DM) is a chronic condition that increases the risk of foot infections, which may lead to gangrene and, in severe cases, lower limb amputation. Transtibial amputation is among the most common procedures, accounting for approximately 85–90% of all limb amputations. The use of a prosthesis is expected to enhance the quality of life (QoL) of post-amputation patients, yet outcomes may vary based on individual factors and causes of amputation. Objective This study aimed to assess the quality of life in patients with transtibial prostheses following amputation due to diabetes mellitus. Methods This descriptive study used observation sheets to evaluate prosthesis usage and the Prosthesis Evaluation Questionnaire (PEQ) to assess quality of life. Participants were transtibial prosthesis users with a history of amputation due to diabetes mellitus. Results Statistical analysis showed a p-value of 0.606 (p > 0.05), indicating no significant difference in quality of life between diabetic amputees and those amputated due to trauma. However, prosthesis use generally contributed to improved mobility and daily functioning. Conclusion While the cause of amputation (diabetes vs. trauma) did not significantly affect overall quality of life, the use of transtibial prostheses supports functional recovery in post-amputation patients. Further research is needed to explore other factors influencing quality of life outcomes in this population.